TANGGUNG JAWAB PELAKU USAHA ATAS KERUSAKAN BARANG YANG MERUGIKAN KONSUMEN MAKANAN RINGAN DI KECAMATAN TANJUNG BARU KABUPATEN TANAH DATAR - Malta, Wahyu Aditiya; Ismi, Hayatul; Darnia, Meriza Elpha (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Technological and economic developments are developing very rapidly, thusinfluencing production activities to be able to meet the increasing and diverseneeds of consumers. Consumers cannot be separated from business actorsbecause they need each other to carry out buying and selling activities. On theother hand, economic growth does not always produce products that comply withsafety standards for consumption and is often detrimental to consumers.However, in reality there are still many business actors operating in the foodsector who do not carry out their rights and obligations properly, thus placingconsumens in weak and disadvantaged position. Such as snack food businessactors who sell their products without paying attention to whether the product isin good condition or not, which cause losses to consumers. So the aim of thisthesis research is first, to analyze the responsibility of business actors for damageto goods that harm snack consumers in Tanjung baru District, Tanah DatarRegency.From the research results it can be concluded the, frist, as regulated inArticle 19 of the UUPK, business actors are obligated to provide compensationfor consumer losses. Secondly,there are legal remedies that consumers can take,namely throught litigation and non litigation. The advice from the author is frist,business actors in running their business actors in running their business must bemore thorought and careful in producing and packaging their products so as notto harm consumers and pay attention to consumer rights and their obligations asbusiness actors. Secondly, consumers must be more careful in purcahsing an itemby checking the condition of the item before purchasing and consuming the foodproduct so that it does not cause harm or harm.Keywords: Business Actor-Damage to Goods-Responsibility